Melting of cryocrystals at high pressures. Computer simulation - Yakub, E.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Simple molecular models were applied to predict melting temperature of highly compressed classical molecular crystals of hydrogen and nitrogen in a wide range of pressures and temperatures using conventional molecular dynamics simulation. It was shown that models which comprise noncentral interaction can reproduce turnover of the melting line observed at megabar pressures. We discuss the relation of this effect to the parameters of chemical bonding.